A Car Buyer's Guide : Advice for consumers when buying a car in Northern Ireland, Republic of Ireland and Great Britain.: Advice for consumers when buying a car in Northern Ireland, Republic of Ireland and Great Britain. ([2018]) - General Consumer Council for Northern Ireland,; European Consumer Centres Network,; Northern Ireland., Department for the Economy,; Trading Standards Service,
No abstract available